Effect of Cement and Compaction on the Physicochemical Behavior of a Material in the Region of Sidi Bel Abbes - Ikhlef, N. S.; Ghembaza, M. S.; Dadouch, M. (Engineering, Technology & Applied Science Research, 2014)
Soil treatment describes the procedure under which a soil acquires certain characteristics that did not originally have. This paper is focused in the field of road earthworks and the treatment of a material found in the region of Sidi Bel Abbes, Algeria. This material has poor characteristics that do not meet the standards used in road geotechnics. To remedy this, firstly, the Proctor Standard characteristics of this material were improved using mechanical treatment that increased the compaction energy. Then a chemical treatment was employed, adding some cement dosages, and results show that the material classified in the A1h class, for an increased maximum dry density and a reduction in water content. A comparative study is made on the optimal properties of the material between the two modes of treatment. On the other hand, after treatment, one finds a decrease in the plasticity index and the methylene blue value. This material exhibits a change of class. Therefore, soil class CL turned into a soil class CL-ML (silt of low plasticity). This observation allows the material to be used as backfill or subgrade.